From re-traumatisation to rightful recourse: designing just and victim-supportive policies for disciplining campus sexual misconduct - Moyo, Grace (Department of Public Law, 2025)
The issue of sexual misconduct in universities has come to a head in South Africa in recent years. Among the concerns that have been raised in student protests, scholarly studies, and research by the Department of Higher Education and Training is the question of effective institutional mechanisms to resolve complaints of sexual misconduct. This research is concerned with the disciplinary processes employed by universities to adjudicate complaints and impose disciplinary measures. The question asked is whether South African universities have policies on sexual misconduct that provide for just and victim-supportive processes, and what measures must be put in place in order for them to do so? My premise for this thesis is that an outcome is just if the determinative method is just, and as such I rely on the theory of Natural Justice and procedural fairness as the framework for developing a just process. I approach this question from a policy perspective, with a focus on developing and implementing policies that lay out disciplinary procedures for sexual misconduct that are responsive to the needs of victims and cognisant of the procedural fairness rights of accused students. I do this by analysing the sexual misconduct policies of thirteen public universities to understand their disciplinary procedures and institutional approaches to sexual misconduct as a whole. I find that, in general, university policies are lacking in so far as providing clear procedural rules and guidelines for disciplinary tribunals that allow for just and victim-supportive adjudication. Current policies provide for an imbalanced adjudication system or do not provide sufficient guidelines for adjudication at all. Ultimately, I make recommendations on how a hybrid model of adjudication can be fashioned; one that takes into account the need for procedural fairness in administrative decision-making, while simultaneously incorporating victim-supportive practices to minimise the trauma that disciplinary processes can inflict on victims of sexual misconduct. Among these recommendations are the inclusion of restorative justice practices in adjudication and sanctioning, the creation of an accusatorial/inquisitorial hybrid model of adjudication, and imposing justifiable limitations on the rules of Natural Justice to create a disciplinary process that is both just and victim-supportive.